2018
DOI: 10.1177/0046958018790831
|View full text |Cite
|
Sign up to set email alerts
|

Doctors’ Job Satisfaction and Its Relationships With Doctor-Patient Relationship and Work-Family Conflict in China: A Structural Equation Modeling

Abstract: The objective of this study was to evaluate the relationship of doctors’ job satisfaction with doctor-patient relationship and work-family conflict in China. The data came from a cross-sectional survey in Hubei province, which was part of China’s Fifth National Health Services Survey conducted in 2013. The survey in Hubei covered 54 secondary and tertiary general hospitals distributed in 20 counties. Of the 1080 questionnaires, 908 were included into our analysis. After surviving from reliability and validity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
52
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(69 citation statements)
references
References 70 publications
3
52
0
2
Order By: Relevance
“…It is not clear from this survey what type of recognition would motivate respondents, since recognition could consist of awards, bonuses for high quality work, or eligibility for promotion. At least two studies have identified recognition as a factor influencing physicians' job satisfaction in China and Mexico 36,37 . Further study needed to determine the relative desirability of different forms of recognition in Bhutan.…”
Section: Discussionmentioning
confidence: 99%
“…It is not clear from this survey what type of recognition would motivate respondents, since recognition could consist of awards, bonuses for high quality work, or eligibility for promotion. At least two studies have identified recognition as a factor influencing physicians' job satisfaction in China and Mexico 36,37 . Further study needed to determine the relative desirability of different forms of recognition in Bhutan.…”
Section: Discussionmentioning
confidence: 99%
“…In some rural areas, transfer can even take up to 1.5 h, which delays effective treatment. Another cause for delay is the complex doctor-patient relationship in China [21, 22]. Primary doctors may need to repeatedly explain disease severity, outcomes, and even costs to patients and families; consult the CSC deputy chief physician through teleconference; and upload video data to determine whether referral is needed.…”
Section: Discussionmentioning
confidence: 99%
“…O nível de satisfação é muitas vezes visto como um outcome que se relaciona com a eficácia de uma organização e o desempenho dentro do ambiente de trabalho. 27 Tem um impacto positivo no nível de intenção de permanecer no trabalho, o que pode ser útil na resolução de problemas de recrutamento e retenção de médicos. 28,29 A satisfação dos médicos inevitavelmente afeta tanto as suas emoções 30 quanto a conciliação trabalho-família.…”
Section: Discussionunclassified